On the night of the shooting star - Hest, Amy; Desmond, Jenni (Somerville, Massachusetts : Candlewick Press, 2017)
Next-door-neighbors Bunny and Dog go about their days as the seasons pass, always noticing one another but never saying hello, until one day, when they are both outside, they see a shooting star that inspires them to try to be friends.
Keywords: Dogs -- Fiction; Rabbits -- Fiction; Friendship -- Fiction; Neighbors -- Fiction